Neoadjuvant and Adjuvant Chemotherapy of Cervical Cancer: Mature Results of the Phase 2 PBM-PFU Protocol. Issue 3 (1st April 2011) - McCaffrey, Rebecca; Bahtiyar, Mert; Kohorn, Ernest I.; Chambers, Joseph T.; Schwartz, Peter E.; Chambers, Setsuko K.
Abstract : Objective: The mature results of the neoadjuvant and adjuvant chemotherapy arms of the nonrandomized, phase 2 Yale University cisplatin, bleomycin, methotrexate, and 5-FU protocol are presented. Methods: Sixty-seven patients were prospectively accrued with a median follow-up of 5.4 years, and standard parameters of toxicity and efficacy were studied. Both univariate and multivariate analyses were applied. Results: The 5-year disease-free survival of 78% for the 25 patients in the adjuvant group, of which 80% had high-risk features including positive margins, parametria, and lymph nodes and 28% had adenocarcinomas, was comparable to recent relevant literature. Only 64% of patients in this group received consolidation radiation therapy, which did not impact on survival. Only 12% of patients recurred distantly. Notably, those who received 4 months or more of chemotherapy had prolonged survival ( P = 0.012). In the neoadjuvant group, chemotherapy response rate among 42 patients (with stages 1B-IIIB cancer) was 79% (50% partial response, 29% complete response), and no patient progressed. In the subgroup of 22 patients who underwent surgery after chemotherapy, 59% had nonsquamous histology. Forty-five percent of patients with stage IIB cancer were deemed operable after chemotherapy. Ninety-five percent received postoperative radiation therapy. There was a 9% pathologic complete response rate, with positive lymph nodes found in 27%. Notably, those who received 3 months or less of chemotherapy had improved overall survival ( P = 0.030). Survival rates of these 22 patients at 3 and 5 years were 73% and 63%, respectively. Although not randomized, these survival rates were similar to those achieved with chemoradiation. Conclusions: Although there are several logistical/design features of the cisplatin, bleomycin, methotrexate, and 5-FU regimen that are not in line with the current chemotherapy era, our experience with this well-tolerated regimen can serve as a proof of principle. Our data suggests that both neoadjuvant and adjuvant cisplatin-based neoadjuvant chemotherapy may have their place. It also raises the possibility that the optimal duration of chemotherapy in adjuvant cases should be longer than in neoadjuvant cases.